2022
DOI: 10.1111/jan.15531
|View full text |Cite
|
Sign up to set email alerts
|

Transition experiences of Middle Eastern midwives into Australian practice: A multiple case narrative study

Abstract: Aim To explore transition experiences of Middle Eastern qualified midwives into practice in Australia. Design This was a qualitative study using multiple case narrative approach underpinned by structuration theory. Methods A total of 19 Middle Eastern qualified midwives from different states of Australia participated in this study. Individual semi‐structured interviews were conducted between November 2020 and September 2021, digitally recorded and then transcribed. Transcriptions were analysed in three stages,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…While the crucial role of nurses in healthcare is well‐acknowledged, there are several underexplored areas of nursing practice that are examined in this special issue. For example, the experiences of disabled nurses (Baker et al, 2023), nurse‐led models of care (Bassah et al, 2023), and the impact of varying interferences on nurses' working memory (Hu et al, 2023). In a scoping review, Baker et al (2023) identified the varying workplace experiences of nurses and midwives with disabilities.…”
Section: Understudied Nursing Phenomenamentioning
confidence: 99%
See 2 more Smart Citations
“…While the crucial role of nurses in healthcare is well‐acknowledged, there are several underexplored areas of nursing practice that are examined in this special issue. For example, the experiences of disabled nurses (Baker et al, 2023), nurse‐led models of care (Bassah et al, 2023), and the impact of varying interferences on nurses' working memory (Hu et al, 2023). In a scoping review, Baker et al (2023) identified the varying workplace experiences of nurses and midwives with disabilities.…”
Section: Understudied Nursing Phenomenamentioning
confidence: 99%
“…For example, the experiences of disabled nurses (Baker et al, 2023), nurse‐led models of care (Bassah et al, 2023), and the impact of varying interferences on nurses' working memory (Hu et al, 2023). In a scoping review, Baker et al (2023) identified the varying workplace experiences of nurses and midwives with disabilities. They illuminated that nurses and midwives can be greatly affected by disability and highlighted the importance of diversity, equity, accessibility and inclusion across the profession (Baker et al, 2023).…”
Section: Understudied Nursing Phenomenamentioning
confidence: 99%
See 1 more Smart Citation